Large-scale interspecific associations and ecological context shape communal roosts of Western jackdaw (Coloeus monedula) - Iñigo Palacios-Martínez; Martina Carrete; Javier García; Hany Alonso; Juan Arizaga; Óscar Frías; Carlos Godinho; Dailos Hernández-Brito; Francisco Hortas; Jesús Martín-Zúñiga; Raymundo Montoya-Ayala; Jorge Mouriño; et al. (PLoS ONE, 2026)
Communal roosting in birds often involves complex interspecific interactions influenced by ecological, social, and environmental factors. We examined winter roosts (n = 232) of western jackdaws ( Coloeus monedula ) across the Iberian Peninsula to assess patterns of species composition, roost sharing, heterospecific abundance, and dominance. Most roosts (71.6%) were shared with other species, primarily corvids, starlings ( Sturnus sp.), and cattle egret ( Ardea ibis ), with an average richness of 2.7 species per roost. Shared roosts hosted significantly more jackdaws than non-shared roosts, with anthropogenic factors (e.g., proximity to landfills and urban areas) positively influencing sharing, whereas elevation, temperature range, and forest cover had negative effects. Shared roosting with cattle egrets, wood pigeons, and starlings increased jackdaw abundance, whereas glossy ibises and high densities of starlings reduced it. Jackdaws were numerically dominant in over half of shared roosts, though dominance was context-dependent and influenced by the abundance of certain associates. These results reveal selective interspecific associations shaped by environmental context and flexible social roles, emphasizing the importance of conserving large communal roosts across diverse habitats to support overwintering bird communities, particularly declining species in open and agricultural landscapes.